2010
DOI: 10.1177/0300985809353311
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Basal Cell Carcinoma in a 7-Week-Old Sprague-Dawley Rat

Abstract: Spontaneous basal cell carcinoma (BCC) is very rare in rats, with an incidence rate of only 0.14% reported in aged animals. A spontaneous BCC occurred in a 7-week-old Sprague-Dawley rat housed in a specific-pathogen-free animal facility. The tumor was a single, well-delineated reddish-brown subcutaneous mass measuring 2 x 2 cm and located in the left inguinal region. Microscopically, the tumor consisted of basaloid cells in lobular and cribriform growth patterns and with a high mitotic rate. Immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…It is also rarely observed in young SD rats. Spontaneous basal cell carcinoma was reported recently in a subcutaneous mass found in the left inguinal region of a young (7-week) SD rat [21, 22]. In the present study, this lesion was only observed in one animal in the middle dose group and did not result in a dose-dependent response.…”
Section: Discussionsupporting
confidence: 65%
“…It is also rarely observed in young SD rats. Spontaneous basal cell carcinoma was reported recently in a subcutaneous mass found in the left inguinal region of a young (7-week) SD rat [21, 22]. In the present study, this lesion was only observed in one animal in the middle dose group and did not result in a dose-dependent response.…”
Section: Discussionsupporting
confidence: 65%
“…The tumor was solitary and likewise showed a strong positivity for CK14 antigen. 13 Basal cell carcinomas have also been induced experimentally in M. natalensis and mice by application of 7,12-dimethylbenz(a)anthracene (DMBA) and 12-0-tetradecanoyl-phorbol-13-acetate (TPA) and other mutagenic chemicals. 14,27 Squamous cell carcinomas have been induced by the same 2-stage skin carcinogenesis (DMBA+TPA) in transgenic mice that carried an oncogene of MnPV.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5,10 The malignant form, basal cell carcinoma (BCC), has a very low incidence of spontaneous occurrence in laboratory rats and mice (0.14% and 0.1%, respectively). 13,17 In domestic animals, BCC is described in cats most frequently. In other domestic animals, BCCs are rare or have not been described.…”
Section: Introductionmentioning
confidence: 99%
“…Most are transgenic mouse models, such as Ptch1 knockout mice ( Arad et al, 2008 ; Aszterbaum et al, 1999 ; Nitzki et al, 2010 ; Skvara et al, 2011 ; So et al, 2004 ), or include constitutive activation of other Hh signaling pathway key regulators, such as oncogenic Smo , Gli1 , or Gli2 mutation expressions driven by skin-specific keratin (K) 5, 6, or 14 promoters (Nitzki et al, 2012). In seven-week-old Sprague-Dawley rats, e.g., spontaneous BCC tumors were observed as single, reddish-brown subcutaneous masses located at the left inguinal region, basaloid cells showed lobular and cribriform growth with high mitotic rates, and cytokeratin 14 and cytokeratin 18 were expressed in nest tumor cells, thereby indicating that spontaneous BCC can occur in young rats ( Lee et al, 2010 ). Nano-electro-ablation methods have been found to induce apoptosis efficiently in a Ptch1 (+/-) K14-Cre-ER p53 fl/fl mouse BCC model ( Nuccitelli et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%